Galvanic vestibular stimulation for postural rehabilitation in neurological disorders: a systematic review - Wei Fu; Ya Bai; Xiaoming Wang (Frontiers in Neuroscience)
BackgroundGalvanic vestibular stimulation (GVS) may potentially improve postural rehabilitation. However, the postural control role of GVS in the neurological disorders has not been systematically reviewed.MethodsWe conducted a systematic review on PubMed, EMBASE, and Web of Science to synthesize key findings of the effectiveness of single and multiple sessions of GVS alone and combined with other interventions on balance in adults with neurological disorders. Diagnosis of neurological disorders, sample size, age and gender of participants, GVS parameters, postural assessments, and study findings were extracted following the PRISMA guidelines. Newcastle-Ottawa scale was used to assess study quality.ResultsTwenty-five studies were included in the systematic review. Clinical application of GVS for postural control included Parkinson’s disease, bilateral vestibulopathy, stroke-induced hemiplegia, multiple sclerosis, progressive supranuclear palsy, persistent postural-perceptual dizziness, and unilateral vestibulopathy. GVS effectively improves postural control in most neurological disorders. Risk of bias assessment showed that most studies had a low risk of bias.ConclusionGVS is a promising complementary therapy to improve postural control and balance in adults with neurological disorders. Future high quality studies should be performed to confirm these findings.